FACTORS AFFECTING PROFITABILITY OF BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Christy, Silvian; Sufiyati , Sufiyati (Graduate Program of Universitas Tarumanagara, 2023)
This study is to analyze how independent commissioners, institutional ownership, number of directors, number of audit committees affect ROA. The banking companies used as samples in this study are 36 companies listed on the Indonesian Stock Exchange for the 2017-2019 period. Purposive sampling method is used as a sampling technique. Multiple linear regression analysis is used in the analysis technique. The results show that only the number of directors has a significant positive effect on profitability (ROA), while profitability (ROA) is not affected by independent commissioners, institutional ownership, and the number of audit committees. The results of this study are expected to provide information to banking companies to be able to increase profitability which has an impact on improving company performance with a focus on good corporate governance.